2023
DOI: 10.1097/wco.0000000000001162
|View full text |Cite
|
Sign up to set email alerts
|

Cortical hyperexcitability in amyotrophic lateral sclerosis: from pathogenesis to diagnosis

Abstract: Purpose of review Identification of upper motor neuron involvement remains a critical component of a diagnosis of amyotrophic lateral sclerosis (ALS), although supportive clinical signs are often not easily appreciated, particularly in the early symptomatic stages of the disease. Although diagnostic criteria have been developed to facilitate improved detection of lower motor neuron impairment through electrophysiological features that have improved diagnostic sensitivity, assessment of upper motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Cortical inexcitability is a well-documented finding in PLS (and late-stage ALS), while cortical hyperexcitability is found in both presymptomatic and early symptomatic ALS, as well as in pure lower motor neurone variants. 7 We note the Newcastle group demonstrated coherence changes in the asymptomatic limb, also supporting subclinical motor cortex dysfunction in the clinically normal hemisphere. 2 Thus, we cannot exclude the possibility that our case, like others previously reported and more classic PLS, will eventually progress to ALS.…”
Section: Hyperexcitability Of the Asymptomatic Motor Cortex In A Case...mentioning
confidence: 62%
“…Cortical inexcitability is a well-documented finding in PLS (and late-stage ALS), while cortical hyperexcitability is found in both presymptomatic and early symptomatic ALS, as well as in pure lower motor neurone variants. 7 We note the Newcastle group demonstrated coherence changes in the asymptomatic limb, also supporting subclinical motor cortex dysfunction in the clinically normal hemisphere. 2 Thus, we cannot exclude the possibility that our case, like others previously reported and more classic PLS, will eventually progress to ALS.…”
Section: Hyperexcitability Of the Asymptomatic Motor Cortex In A Case...mentioning
confidence: 62%
“…In ALS, an imbalance between cortical excitation and inhibition has been identified in the motor cortex of animal models, 42 including the SOD1 G93A model, 35,65 and in both sporadic and familial ALS patient cohorts 12,62,66 . This imbalance underlies cortical hyperexcitability and is hypothesised to contribute to the disease pathogenesis through overactivation and excitotoxic damage to motor neurons 13,14,67 . It is therefore plausible that the increased levels of NPY in the ALS motor cortex, influence the electrophysiological properties and function of the cortical motor pathways in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Using TMS, to measure the ipsilateral silent period, it has been shown that loss of callosal inhibition is a sensitive and early marker of disease activity in ALS ( Hübers et al, 2021 ). CC hyperexcitability in early stages of disease might explain how TDP-43 aggregation spreads from one hemisphere to another ( Hübers et al, 2021 , Timmins et al, 2023 ). A reduction of transcallosal inhibition is associated with features indicative of cortical hyperexcitability, including reduction of short interval intracortical inhibition and increased in short interval intracortical facilitation.…”
Section: Extra Motor Pathologymentioning
confidence: 99%
“…A reduction of transcallosal inhibition is associated with features indicative of cortical hyperexcitability, including reduction of short interval intracortical inhibition and increased in short interval intracortical facilitation. Reduction in transcallosal inhibition is also correlated with the rate of disease progression ( Timmins et al, 2023 , van den Bos et al, 2021 ).…”
Section: Extra Motor Pathologymentioning
confidence: 99%